Kepribadian dan Emosi Tokoh Utama dalam Novelet Menunggu Beduk Berbunyi Karya Hamka - Silvi Mardiana; Rika Listya Nuraini (Institut Agama Islam Negeri Curup, 2020)
This study discusses the psychological aspects of the main character. The purpose of the study is to explain the understanding and details in depth about the personality and emotional classification of the main character. This is a descriptive qualitative study. The approach used is literary psychology. The documentation technique by means of reading and taking notes is used to obtain data from Hamka's novelette entitled â€œWaiting for the Soundingâ€. The content analysis technique is used in this study to find information and in-depth understanding of the data collected. Data validation uses theory triangulation. The results and discussion show that Mr. Sharif's personality is influenced by the id, the ego, and the superego. Mr. Sharif in the novelette is described as having a lonely character and suffering from the life he lived. He worked as a Dutch employee in order to escape the misery of the colonial period at that time. Therefore, it seems that Mr. Sharifâ€™s various emotions demonstrate a form of conflict both with oneself (internal conflict) in the form of regret and feelings of guilt and with the environment (external conflict) in the form of love, envy and hate, and loneliness